THE EFFECTS OF SODIUM PERCARBONATE CONCENTRATION AND AMOUNT OF WATER IN THE CHAMOIS TANNING ON THE CHAMOIS LEATHER QUALITY - Ono Suparno dan Eko Wahyudi (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACTChamois leather is a popular product in trading, because it has specific uses. Nowadays, oxidation process of chamois leather production is time consuming, i.e. about two weeks. This causes production process of chamois leather needs long time. In this study, the effects of sodium percarbonate concentration and amount of water in the chamois tanning on the chamois leather quality were investigated. This study shows that sodium percarbonate amount significantly affected thickness and oil content of the leathers; amount of water significantly affected oil content of the leather; meanwhile, the interaction between sodium percarbonate concentration and amount of water significantly affected ash and oil contents of the leathers. The optimum condition for the oxidation was sodium percarbonate concentration of 4% and amount of water of 50%. The physical properties of the leather were thickness of 0.87 mm, tensile strength of 35.95 N/mm2, elongation at break of 129%, tear strength of 82.01 N/mm, water absorption of 226% (2 hours), and 303% (24 hours). The chemical properties were pH of 7.45, oil content of 8.1%, and ash content of 1.3%. The organoleptic properties were good, i.e. softness of 6-7, colour of 7- 8, and odour of 7- 8.Keywords: chamois leather, oxidation, rubber seed oil, sodium percarbonate, water